Change in Children’s Self-Concept, Body-Esteem, and Eating Attitudes Before and 4 Years After Maternal RYGB - Sellberg, Fanny (Obes Surg, 2018)
INTRODUCTION: The aim of the present study was to look at longitudinal changes in children’s self-concept, body-esteem, and eating attitudes before and 4 years after maternal RYGB surgery. METHODS: Sixty-nine women and 81 appurtenant children were recruited from RYGB waiting lists at 5 hospitals in Sweden. Families were visited at home pre-surgery, 9 months, and 4 years post-maternal RYGB to measure BMI. Furthermore, all participating family members completed questionnaires. Mothers’ questionnaires measured eating behavior, depression, anxiety, and sleep quality, and children’s questionnaires measured body-esteem, self-concept, and eating attitudes. RESULTS: Thirty-five/sixty-nine mothers and 43/81 children participated in all 3 measurements. Mothers reduced their BMI from pre-surgery (39.2) to 9 months (27.0) and 4 years post-surgery (27.4). Children’s prevalence of overweight/obesity was lower 9 months post-surgery (48.8%) but at the same levels again 4 years post-surgery (58.1%), compared to pre-surgery (58.1%). The same rebound pattern was seen among children’s eating attitudes, mothers’ symptoms of depression and anxiety, and sleep quality. We found no correlations between mothers’ BMI or eating behavior and children’s BMI or eating behavior. CONCLUSION: Children’s prevalence of overweight/obesity and eating attitudes improves soon after their mothers’ RYGB, but then return to pre-surgery levels at 4 years post-surgery, as do mothers’ sleep quality and symptoms of depression and anxiety, even though their weight loss was maintained. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11695-018-3348-z) contains supplementary material, which is available to authorized users.